EFFORT AS RESPONSIBILITY - Jenkins, David (2023)
John Roemer has created a model by which the luck egalitarian distinction between choice and luck can be used to motivate real policy decisions. By dividing society into ‘types’, Roemer suggests we are able to limit comparisons made between different people to that which they are able to control. In so doing, responsible individual action becomes the sole means by which inequalities can be justified and far more transformative redistributive legislation can be motivated. However, the model relies on two types of comparison – both within and between types – that ultimately flaw Roemer’s claims to be measuring responsible action. The model assumes that it is unproblematic to compare effort across individuals who are situated in radically unequal circumstances; it also assumes that the type can control for circumstances in a way that ignores the enormous contingency that constitutes human life. As a consequence, Roemer’s ambitious proposal fails to practically apply the choice-luck distinction